2007
DOI: 10.1518/001872007x200120
|View full text |Cite
|
Sign up to set email alerts
|

Recovery From Virtual Environment Exposure: Expected Time Course of Symptoms and Potential Readaptation Strategies

Abstract: These findings may serve as a guide in the development of monitoring policies following VE exposure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
47
2
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(50 citation statements)
references
References 28 publications
0
47
2
1
Order By: Relevance
“…These experiences showed the effects of pushing buttons repeatedly but also demonstrate how simulations of body movements in virtual environments can have similar effects. Previous research has found neural adaptation effects after the exposure to virtual environment simulators such as the reduction of complex psychomotor flexibility, and reduced motor control (e.g., Champney et al, 2007). The data also suggest that gamers' behaviours have been conditioned to respond in certain way to stimuli and events, and that some gamers experienced difficulty in controlling their impulses.…”
Section: Discussionmentioning
confidence: 59%
“…These experiences showed the effects of pushing buttons repeatedly but also demonstrate how simulations of body movements in virtual environments can have similar effects. Previous research has found neural adaptation effects after the exposure to virtual environment simulators such as the reduction of complex psychomotor flexibility, and reduced motor control (e.g., Champney et al, 2007). The data also suggest that gamers' behaviours have been conditioned to respond in certain way to stimuli and events, and that some gamers experienced difficulty in controlling their impulses.…”
Section: Discussionmentioning
confidence: 59%
“…Firstly, particular attention should be paid to young adults, and students in terms of GTP, Secondly, it is important to regulate gaming habits since it is expected that gamers are more susceptible to committing cognitive failures due to mental fatigue after prolonged playing (Van den Linden et al, 2003), as well as prolonged videogame sessions that may enhance the effects of neural adaptations where duration is proportional to the exposure (Champney et al, 2007). Moreover, playing videogames before going to bed has been associated with deficits in sleep quality (Dworak et al, 2007;Higuchi et al, 2005;King et al, 2013) that in turn can compromise the gamers' cognitive control, making them more susceptible to experience GTP.…”
Section: Discussionmentioning
confidence: 99%
“…More specifically, longer gaming sessions may enhance the effects of neural adaptation (e.g., motion sickness, cybersickness, visual motion after-effects, etc.) (Dyson, 2010;Kennedy, Stanney, & Dunlap, 2000), where duration is proportional to exposure time (Champney et al, 2007). In addition, gaming has been correlated with sleep deprivation (Achab et al, 2011;Choi et al, 2009;Rehbein, Kleimann, & Mossle, 2010;Tazawa & Okada, 2001).…”
Section: Gaming Habitsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this paper, mitigation and readaptation may be used interchangeably, as both describe an action or a strategy to quicken one's recovery from motion sickness. Motion sickness mitigation techniques include taking medications, wearing motion sickness bands (Estrada et al, 2007), and hand-eye coordination tasks (Champney et al, 2007). Readaptation will be addressed in the hypothesis section of this chapter and a more detailed examination of mitigation techniques and readaptation strategies can be found in Chapter 2.…”
Section: Mitigationmentioning
confidence: 99%